MEDB-74. Serial assessment of measurable residual disease in medulloblastoma liquid biopsies. (3rd June 2022) - Northcott, Paul; Smith, Kyle; Kumar, Rahul; Paul, Leena; Bihannic, Laure; Lin, Tong; Maass, Kendra; Pajtler, Kristian; Chintagumpala, Murali; Su, Jack; Bouffet, Eric; Fisher, Michael; et al.
Abstract: Nearly one-third of children with medulloblastoma, a malignant embryonal tumor of the cerebellum, succumb to their disease. Conventional response monitoring by imaging and cerebrospinal fluid (CSF) cytology remains challenging and a marker for measurable residual disease (MRD) is lacking. Here, we show the clinical utility of CSF-derived cell-free DNA (cfDNA) as a biomarker of MRD in serial samples collected from children with medulloblastoma (123 patients, 476 samples) enrolled on a prospective trial. Using low-coverage whole-genome sequencing, tumor-associated copy-number variations (CNVs) in CSF-derived cfDNA are investigated as an MRD surrogate. MRD is detected at baseline in 85% and 54% of patients with metastatic and localized disease, respectively. The number of MRD-positive patients decline with therapy, yet those with persistent MRD have significantly higher risk of progression. Importantly, MRD detection precedes radiographic progression in half who relapse. Our findings advocate for the prospective assessment of CSF-derived liquid biopsies in future trials for medulloblastoma.